Colorimetric and fluorometric bimodal amine chemosensor based on deprotonation-induced intramolecular charge transfer: Application to food spoilage detection - Oh, Byeong M.; Cho, Na Young; Lee, Eun Hye; Park, Seon Young; Eun, Hyeong Ju; Kim, Jong H. (Journal of Hazardous Materials, 2024)
Amine derivatives are signature organic compounds generated from rotten protein food. Thus, sensitive detection of the presence of amines in protein foods can be a critical technique for monitoring their quality. In this study, we develop an organic chemosensor probe, 4-(2-(3-(dicyanomethylene)− 5,5-dimethylcyclohex-1-en-1-yl)vinyl)-N,N-diethylbenzenaminium chloride (DEAH), to effectively detect amines through discernible bimodal (colorimetric and fluorometric) changes. By exploiting the amine-triggered intramolecular charge transfer behavior, DEAH exhibits rapid color changes (<1 s) with an excellent detection limit (36.9 nM) and also fluorescence turn-on in response to amine gas. Moreover, it possesses detection capabilities in versatile conditions, including solutions, solids, and coated films, suggesting its practical applicability. In particular, DEAH shows dramatic color change from yellow to violet with exceptional color difference (△Eab) over 98, repeatable usability, and excellent selectivity to amines. Based on these compelling advantages, we successfully demonstrate real-time monitoring of amine gas generated from spoiled protein foods using DEAH-coated films.
Keywords: Amine gas; Chemo-sensors; Color changes; Colorimetric chemosensor; Fluorometric chemosensor; Food spoilage; Food spoilage sensor; Intra-molecular charge transfer; Intramolecular charge transfers; Protein food; Amines; Colorimetry; Fluorometry; Food; Spectrometry, Fluorescence; Amine gas; Colorimetric chemosensor; Fluorometric chemosensor; Food spoilage sensor; Intramolecular charge transfer